Peas as feed for dairy cows - Galméus, David (SLU/Dept. of Animal Nutrition and Management (until 231231), 2012)
Abstract An approaching overproduction of cereals and a future uncertain supply of non genetic modified vegetable protein feedstuffs have increased the interest in an expansion of the domestic production of protein feedstuffs in Norway. Besides rapeseed (Brassica campestris), peas (Pisum sativum) may be the most suitable crop for this purpose. Peas are characterized by having a relatively high content of crude protein, ranging between 20-26%, a high content of starch, 42-51%, and a low content of fat. In general, the energy value for peas is higher than for barley but lower than for rapeseed and soybean meal. Pea protein consists of albumins and globulins to 85-100%, which leads to the fact that a large part of the pea protein is soluble and degradable in the rumen. Starch in peas is on the other hand to a large extent resistant to rumen degradation compared to starch from other starch rich feedstuffs. To decrease the ruminal degradability of dietary protein, and by means of that increase the total flow of amino acids to the small intestine, several processing methods are used. These methods are often based on some kind of heat treatments, which result in so called Malliard reactions. Expanding is one of these heat treatments, which earlier has shown to decrease the ruminal degradation of concentrates consisting of peas. The amino acid profile in peas is characterized by a high content of lysine but a low content of the sulphur containing amino acids cysteine and methionine. There are no earlier experiences from trials in Norway, where peas are used as a feed for dairy cows. To increase the knowledge of the effect when peas are fed in large amounts to dairy cows, an in vivo-trial has been performed within the project "Alternative protein rich concentrate feedstuffs" (Alternative proteinrike kraftfôrråvarer) at the Department of Animal and Aquacultural Sciences at Norwegian Life Science University. The trial was performed with four dairy cows with rumen and intestinal fistulas in a Latin square design with four treatments and four periods. Treatments with extruded and pelleted concentrates were compared, which, with the exception for a base mixture, consisted of 1) 12% soybean meal, 15.6% barley, 5.4% oats and 3.8% of a Ca-bonded fat source (Aco Feed Gigant) (S), 2) 10% full fat rapeseed and 27% peas (PR), 3) 10% full fat rapeseed, 19.9% barley and 6.9% oats (R), and 4) a blend of concentrate mixture S and PR in a ratio 6 of 50:50 (SPR). The fat content was planned to be equal among all concentrate mixtures and the content of N equal among S, PR and SPR. All experimental concentrates were extruded at 103-107° C, and thereafter pelleted at 70-75° C. Peas in combination with full fat rapeseed did not affect the dry matter intake of feed. Only a small variation in ruminal pH and fermentation products was detected among concentrate mixtures. The ammonia concentration in milk, which is usually used as an indicator for ruminal protein degradability, was however higher for PR which represented the highest pea content. On the other hand, no higher values of blood urea levels were detected for PR compared to the other treatments. Although the amino acid profile in the dietary protein differed among treatments, there were only a small difference detected of the amino acid profile in the protein in rumen microbes and the total protein fraction flowing to the duodenum. There were only small variations in the digestibility coefficients in the rumen and small intestine and in the flow of single nutrients to the duodenum. However, there was a tendency for increased flow of total N fraction to the duodenum for S than for PR. The exchange of peas on behalf of cereals which was the fact for addition of peas in PR compared to R tended to counteract the depression in ruminal digestibility of dry matter and NDF, which was the fact for R. The production results were affected by frequent clinical mastitis, and therefore quite insecure. However, on basis of present data, there was a decrease in daily production of ECM and a decrease in milk protein content for R. When cereals were substituted by peas, the daily production of ECM was not increased to the same level as that of the S and SPR. With focus on milk production, the optimal concentrate seemed to be a mixture of soybean meal and cereals or soybean meal and cereals in combination with peas and rapeseed.